SARS-CoV-2: A virus that is shaking the world - Shankar, Pathiyil Ravi (Journal of KIST Medical College, 2020)
The coronavirus disease -19 and the causative virus, SARS-CoV-2 has had a profound impact globally during the year 2020. The virus has spread to over 213 countries and has created a climate of fear and uncertainty. In this article the author reflects on the pandemic, its effects and also the impact of measures to contain the virus.